Inside Back Cover: Electrostatic Assembly/Disassembly of Nanoscaled Colloidosomes for Light‐Triggered Cargo Release (Angew. Chem. Int. Ed. 23/2015). Issue 23 (21st May 2015) - Li, Song; Moosa, Basem A.; Croissant, Jonas G.; Khashab, Niveen M.
Abstract : Electrostatically assembled colloidosomes are promising hollow carriers for the encapsulation and release of large cargos on demand. In their Communication onpage 6804 ff., N. Khashab et al. describe nanoscale colloidosomes that are composed of oppositely charged organosilica nanoparticles (NPs). Upon light irradiation, a photoreaction of the organosilica NPs can reverse the charges of the NPs, leading to disassembly of the capsules and light‐triggered release of the payload.